INTEGRASI THEOLOGIA DAN POLITIK - Ferdinan S. Manafe (Jurnal Arrabona, 2018)
This work explore the difference between theology and politics, the impact of theology into politics and the integration of theology and politics. Politics might not be avoided in its positive meaning and when it does not violate morality and religious norm in its practise. If politics has nothing to do with God (read: theology) or avoids it, then its methods, even its rules, are surely wrong and its implementation will, therefore, be far away from good ethics. Put in another way, all human efforts both in politics and theology should be understood and applied integratively for both are essentially one. This integrative knowledge will grant positive impact in its implementation. It is recommended to church leaders and lay men to understand the integration of theology and politics and to give positive impact on the society.